Anti-inflammatory activity of grapefruit juice in an in vivo model of ulcerative colitis: Comparability studies of unprocessed and bioprocessed juices. (December 2019) - Mendes, Carla; Rocha, João; Direito, Rosa; Fernandes, Adelaide; Sepodes, Bruno; Figueira, Maria-Eduardo; Ribeiro, Maria H.
Graphical abstract: Highlights: Rhamnopyranosidase and pectinase were successfully co-encapsulated in chitosan plus calcium aalginate beads. Grapefruit juice enzymatic processing allowed a reduction of 75% in naringin and 90% in pectin. Graprefruit juice showed a high anti-inflammatory effect in in vivo model of ulcerative colitis. Anti-inflammatory effect of unprocessed and bioprocessed grapefruit juice was observed. Grapefruit juice is a promising candidate for the health promotion in the inflammatory bowel disease. Abstract: Citrus fruits are one of the most consumed fruit juice in the world. They are widely accepted for their pleasant and nutritive value. The interest in fruit juice bioactive compounds has increased due to its health benefits, namely protection against inflammatory, cardiovascular or neurodegenerative diseases, among others. Inflammatory bowel diseases are chronic inflammatory diseases of the gastrointestinal tract, characterized by chronic recurrent ulceration of the bowels. Therefore, the main goal of this work was to study the effect of (un)processed grapefruit juice on biological efficacy, in an in vivo model of induced ulcerative colitis, as model of anti-inflammatory activity. Comparability studies of unprocessed and bioprocessed grapefruit juices were carried out. The juice was processed with co-encapsulated pectinase and rhamnopyranosidase in hydrogels. The co-encapsulation of the enzymes in chitosan plus calcium alginate beads showed a high residual activity (98%), being effective in clarifying grapefruit juice and reducing bitterness (75%). A significant decrease (>80%) on the mice intestine inflammation (p < 0.001) showed the high anti-inflammatory properties of grapefruit juices, unprocessed and bioprocessed.